Role of Pharmacist in Nutrition Management-The Unexplored Path - Singla, Neelam; Jindal, Avani; Mahapatra, Debarshi Kar (Indian Journal of Pharmacy Practice)
Public health aims at improving the health and well-being of populations, reducing health inequalities, and ensuring the sustainability of health systems. The prevention of disease is anticipated to be a more cost-effective and long-term method of reducing disease burden. One of the most important strategies for reducing this burden is nutrition management. The problems surrounding nutrition and its management are often multi-dimensional. It demands a trained workforce, forming strong alliances with the same goal, and being able to communicate effectively with all the stakeholders. Fixing the role and responsibility of pharmacists is the logical answer to address India’s multidimensional nutritional challenge now and in the future. One of the critical components in managing acute and chronic diseases and overall public health is nutrition management but it requires knowledge about the importance of a balanced diet, food, and nutrition-related health concerns, drug usage, drug-drug interactions, drug-food interactions, drug-nutrient interactions, food supplements, dietary supplements, nutraceuticals, cost-effective treatments, etc. This article aims to demonstrate pharmacists’ knowledge, attitude, understanding, and professional skills to tackle the issue of nutrition management by assuring cost-effective healthcare choices, offering evidence-based advice on nutritional products and therapies, management of health supplements and nutraceuticals, and advising on drug-drug, drug food, and drug-nutrient interactions.
Keywords: Pharmacist; Nutrition management; Lifestyle diseases; Anatomy and physiology; Nutritional supplements; Nutraceuticals